Learning Motivation, Learning Facilities and Parental Support as Predictors of Agricultural Vocational Students Learning Outcomes in Takalar District - Hijrahwati Hijrahwati; Jamaluddin Jamaluddin; Mustari Lamada (Jurnal Pendidikan Terapan, 2026)
Objective: This study examines the predictive contribution of learning motivation, learning facilities, and parental support to learning outcomes among agricultural vocational students in Takalar Regency. Method: Using a quantitative ex-post facto design, 135 students from agricultural programs (ATPH, APHP, ATP) at vocational schools in Takalar Regency were involved. Motivation, facilities, and parental support were measured via questionnaires; learning outcomes were obtained from documented average grades. After outlier screening removed 14 cases, the final analytic sample was 121 students. Data were analyzed using multiple linear regression, with 95% confidence intervals reported for all coefficients. Findings: The model was significant, F(3, 117) = 5,950, p < .001, explaining 13,2% of the variance in learning outcomes (R² = .132). Learning motivation (B = -0.052, β = -.095, p = .298, 95% CI [-.151, .047]) and Learning facilities (B = -0.079, β = -.113, p = .216, 95% CI [-.205, .047]) showed no significant relationship with learning outcomes. Parental support was a significant negative predictor (B = -0.114, β = -.358, p < .001, 95% CI [-.168, -.060]), a statistical association that should not be read as causal. Research Implications: Recommendations should focus on the proportionality and form of parental involvement rather than generalized integrated school-teacher-parent support, since motivation and facilities were non-significant and the model's explanatory power remains low. Conclusions are preliminary and require further study. Value: This study fills a gap in simultaneous empirical research on these three variables among agricultural vocational students in Takalar Regency, a context still rarely examined.